Simulations on recoverability performances for a coalbed methane field in SE edge of Ordos basin, China. (1st December 2018) - Zou, Mingjun; Wei, Simin; Huang, Zhiquan; Lv, Xiaochun; Guo, Biao
Highlights: Simulations on recoverability performances for two single wells are conducted. Optimizations for three types of candidate rectangular well spaces are simulated. Fifteen years' field simulation under well space of 350 × 300 m is conducted. Analyses of recoverability and economic profit are used to validate the space adopted. Abstract: This paper mainly studies the recoverability performances for a coalbed methane (CBM) field located in the southeastern edge of the Ordos basin of China. Geological models are established, and drainage performances for four typical wells are described in detail. Single well simulations for the four wells are conducted to check accuracies of parameters and predict well drainage performances, and optimizations of well spaces are simulated to determine the most suitable well space. Results indicate that the reservoir parameters used in this study are quite accurate, and the well space of 350 × 300 m is most suitable in this area. Furthermore, the fifteen years' field simulation under the well space of 350 × 300 m is conducted, which shows that the well number, average production and cumulative production are 1944, 7.01 × 10 8 m 3 /d and 105.22 × 10 8 m 3, respectively. To validate the well space used in this study, analyses of recoverability and economic profit are conducted, both of which demonstrate that the well space of 350 × 300 m is most suitable in this area and can bring a stable drainage performance for a long time and get a high gas production.